Boys from County Hell - Rowan, Jack, 1997-; O'Neill, Nigel; Harland, Louisa; Lynch, John, 1961-; Baugh, Chris; Shudder Films; Endeavor Content (Firm); Fis Eireann/Screen Ireland (Firm); Northern Ireland Screen (Firm); Automatik (Firm); Egg Studios; Inevitable Pictures; et al. (Place of publication not identified Shudder, 2021)
Strange events unfold in Six Mile Hill when construction on a new road disrupts the ancient burial ground of Abhartach, a legendary Irish vampire said to have inspired Bram Stoker's famed 'Dracula.' Deadly and sinister forces terrorize the construction crew, and they're forced to fight to survive the night while exposing the true horror that resides in the town's local myth.
Originally released as a motion picture in 2021.
Wide screen.
Director of photography, Ryan Kernaghan; editor, Brian Phillip Davis.
Jack Rowan, Nigel O'Neill, Louisa Harland, John Lynch.
Blu-ray, wide screen; requires Blu-ray player.
114926
Keywords: Vampires -- Drama; Construction workers -- Drama; Blu-ray discs; Vampire films; Comedy films; Drama; Feature films; Fiction films; Horror films